Kapitały własne a rezerwy techniczno-ubezpieczeniowe jako podstawowe źródła finansowania działalności zakładów ubezpieczeń - Chmielowiec-Lewczuk, Magdalena (Own Capitals versus Technical Reserves as the Main Sources of Financing Insurance Companies Activities., 2006)
Financing of insurance companies activities bases on two sources: capital and technical reserves. The article presents a short description of the character of Polish insurance companies in the context of their capital structure. The capital is an internal source of financing while technical reserves are the exterior one. There are a lot of insurance companies on the Polish insurance market which are very similar or completely different one to another. The article presents an analysis of different groups of insurance companies which includes insurance companies in total, non-life insurance companies, life insurance companies, insurance companies with majority of domestic capital, insurance companies with majority of foreign capital, in the form of joint-stock companies and insurance companies in the form of mutual insurance societies.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1109, s. 116-123